Comparison of Parental Communication Patterns on Empathy in Children Aged 3-6 - Dian Cahyani; Rose Mini Agoes Salim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Empathy is a key component in the social-emotional development of early childhood, which is influenced by communication patterns within the family. This study aims to analyze the influence of parental communication patterns on the empathy of children aged 3–6 years. The study used a quantitative approach with a correlational method on 69 pairs of parents. The data were analyzed using Pearson's correlation test and multiple linear regression. The results show that conversation-oriented communication patterns have a positive and significant relationship with children's empathy, both in mothers and fathers, while conformity-oriented patterns have a significantly negative relationship. Mothers' conversation orientation contributes most strongly to increasing children's empathy, while fathers' conformity orientation has a greater negative impact. These findings confirm the different roles of maternal and paternal communication in shaping early childhood empathy. Theoretically, this study reinforces the model of family communication patterns in the context of empathy development. Practically, the results provide an empirical basis for parents and early childhood educators to implement more dialogic communication strategies to foster empathy from an early age.